1994
DOI: 10.1111/j.1365-2133.1994.tb03420.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium complex infection limited to the skin in a patient with systemic lupus erythematosus

Abstract: We describe a case of Mycobacterium avium infection of the skin in a 51-year-old woman with systemic lupus erythematosus. Two lesions were treated with a combination of oral tetracycline or minocycline and hyperthermia using a portable warmer. One subsequently healed, leaving an atrophic scar, but the other lesion persisted, and was eventually excised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 18 publications
0
8
0
2
Order By: Relevance
“…26 MAC are also ubiquitous in the environment, 27 but cutaneous infection due to MAC are unusual; when it does occur, there are variable appearances such as multiple ulcers, 28 abscesses, 29 painless nodules, plaques resembling lepromatous leprosy, 30 ecthyma-like lesions, prurigo nodularis-like lesions, 31 erythematous masses with matted lymph nodes 32 and rosacea-like lesions, 33 all predominantly in immunosuppressed patients. [33][34][35] Disseminated disease is also associated with such immunosuppression, and on rare occasions cutaneous lesions may also be present. Therapy of MAC infection is difficult because of the frequent resistance of isolates to antibiotics, but in localized forms of disease, surgery may be curative.…”
Section: Discussionmentioning
confidence: 99%
“…26 MAC are also ubiquitous in the environment, 27 but cutaneous infection due to MAC are unusual; when it does occur, there are variable appearances such as multiple ulcers, 28 abscesses, 29 painless nodules, plaques resembling lepromatous leprosy, 30 ecthyma-like lesions, prurigo nodularis-like lesions, 31 erythematous masses with matted lymph nodes 32 and rosacea-like lesions, 33 all predominantly in immunosuppressed patients. [33][34][35] Disseminated disease is also associated with such immunosuppression, and on rare occasions cutaneous lesions may also be present. Therapy of MAC infection is difficult because of the frequent resistance of isolates to antibiotics, but in localized forms of disease, surgery may be curative.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms consisted of indurations and subcutaneous abscesses resembling those of scrofuloderma in nine cases (3,(5)(6)(7)22,23), ulceration in 5 cases (2,14,17,19,21), lesions similar to those of lupus vulgaris in 3 cases (4,8,26), and multiple intradermal or subcutaneous nodules in 10 cases (9-13, 15, 16, 18). Of the total of 29 cases, there were four (2,23) in whom the lesions appeared as a complication of AIDS, four (10,11,20,22) in whom lesions developed during long-term administration of corticosteroids for diseases such as systemic lupus erythematosus, two that were complications of diabetes mellitus (17,21), one that was treated by radiotherapy (26), and 17 cases in which neither the presence of a disease nor the administration of a drug likely to cause immunosuppression was a factor.…”
Section: Discussionmentioning
confidence: 99%
“…The 29 cases in Table 1 that were reported before ours included 12 in which the pathogen was recognized in the tissues. The staining methods used were the Ziehl-Neelsen technique in seven cases (5,8,11,13,15,26), fluorescent staining in two cases (19,21), and the Fite method in one (20). In two cases (2), the technique was not reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermotherapy has been attempted for the rarely encountered skin-limited MAC, showing only partial therapeutic efficacy. 99 In a patient with systemic lupus erythematosus and three isolated lesions consistent on histopathology and culture with MAC, one lesion resolved spontaneously after 6 months, one lesion resolved with local hyperthermia via a portable warmer on the lesion ''from time to time'' in combination with tetracycline followed by minocycline, and one lesion was excised after it did not resolve with 3 months of antimicrobial therapy and thermotherapy. An earlier Japanese study including two cases of MAC infection of the skin indicated that thermotherapy was ineffective against MAC, likely because MAC requires a higher optimum temperature than the more heatsensitive M marinum.…”
Section: Mycobacterium Avium Complexmentioning
confidence: 98%